Cytotoxic Lipopeptide Muscotoxin A, Isolated from Soil Cyanobacterium Desmonostoc muscorum, Permeabilizes Phospholipid Membranes by Reducing Their Fluidity - Tomek, Petr; Hrouzek, Pavel; Kuzma, Marek; Sýkora, Jan; Fišer, Radovan; Černý, Jan; Novák, Petr; Bártová, Simona; Šimek, Petr; Hof, Martin; Kavan, Daniel; Kopecký, Jiří (Chemical research in toxicology, 2015)
There is mounting evidence that cyanobacterial lipopeptides can kill mammalian cells, presenting a hazard to human health. Unfortunately, their mechanism of toxicity is poorly understood. We have isolated new cyclic undeca-lipopeptides muscotoxin A and B containing unique lipophilic residue 3-amino-2,5-dihydroxydecanoic acid (5-OH Ahdoa). Muscotoxin B was not used for biological studies due to its poor yield. Muscotoxin A was cytotoxic to YAC-1, Sp/2, and HeLa cancer cell lines (LC50 ranged from 9.9 to 13.2 μM after 24 h of exposure), causing membrane damage and influx of calcium ions. Subsequently, we studied this lytic mechanism using synthetic liposomes with encapsulated fluorescent probes. Muscotoxin A permeabilized liposomes composed exclusively of phospholipids, demonstrating that no proteins or carbohydrates present in biomembranes are essential for its activity. Paradoxically, the permeabilization activity of muscotoxin A was mediated by a significant reduction in membrane surface fluidity (stiffening), the opposite of that caused by synthetic detergents and cytolytic lipopeptide puwainaphycin F. At 25 °C, muscotoxin A disrupted liposomes with and without cholesterol/sphingomyelin; however, at 37 °C, it was selective against liposomes with cholesterol/sphingomyelin. It appears that both membrane fluidity and organization can affect the lytic activity of muscotoxin A. Our findings strengthen the evidence that cyanobacterial lipopeptides specifically disrupt mammalian cell membranes and bring new insights into the mechanism of this effect.